2009
DOI: 10.1130/g25373a.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic evolution of the Edwards Aquifer recharge zone (Balcones fault zone) as recorded in the DNA of eyeless Cicurina cave spiders, south-central Texas

Abstract: The Balcones Escarpment of south-central Texas is the eroded topographic expression of an en echelon fault zone where Cretaceous carbonates have been modifi ed by karst processes infl uenced by structural and stratigraphic controls. While the modern confi ned Edwards Aquifer fl ows through cavernous voids at the base of the escarpment, air-fi lled caves perched in the escarpment are relicts of paleoaquifer hydrology. The structural geology of the Balcones Escarpment and the phylogeography of its endemic cave s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Similar radiations are known for Cicurina spiders (Paquin and Dupérré 2009; Paquin and Hedin 2004) and Texella harvestmen (Ubick and Briggs 1992, 2004) both of which show similar biogeographic patterns and affinity for caves. Recent work has shown that the diversification patterns of Cicurina is correlated with the complex faulting in the region (White et al 2009) and may serve as a general model to explain the diversity of the Texas cave fauna. On-going work has been directed at synthesizing the distributions for multiple cave invertebrates in order to develop a comprehensive understanding of the Texas fauna (Reddell et al in prep.…”
Section: Discussionmentioning
confidence: 99%
“…Similar radiations are known for Cicurina spiders (Paquin and Dupérré 2009; Paquin and Hedin 2004) and Texella harvestmen (Ubick and Briggs 1992, 2004) both of which show similar biogeographic patterns and affinity for caves. Recent work has shown that the diversification patterns of Cicurina is correlated with the complex faulting in the region (White et al 2009) and may serve as a general model to explain the diversity of the Texas cave fauna. On-going work has been directed at synthesizing the distributions for multiple cave invertebrates in order to develop a comprehensive understanding of the Texas fauna (Reddell et al in prep.…”
Section: Discussionmentioning
confidence: 99%
“…Constraints of space prescribe a detailed summary of similar research along steep topography in New Zealand's Southern Alps, which exploited the phylogeographic records in galaxiid fishes to reconstruct finer-scaled details of landform evolution Craw et al, 2008). Yet another example exploited the tight ecological stenotopy of cave-dwelling spiders in a karstic landscape, to reconstruct when principal episodes of tectonics uplifted the southeast margin of North America (White et al, 2009). …”
Section: Tracking Formative Events Along the Plateau's Edgementioning
confidence: 98%
“…Karstification of the Edwards Plateau began at least 6 MYA within faulted and down‐dipping Cretaceous limestone along the margin of the Gulf of Mexico sedimentary basin (White et al. ). As aquifers evolve downward within Cretaceous‐age limestone (Deike , White et al.…”
Section: Introductionmentioning
confidence: 99%
“…As aquifers evolve downward within Cretaceous‐age limestone (Deike , White et al. ), surface streams and rivers continuously erode and intercept confining layers of the aquifer, forming and later bypassing artesian springs (Woodruff and Abbott , Grimshaw and Woodruff ). Consequently, artesian springs in arid and semi‐arid regions of the Edwards Plateau provide perennial flows that are moderately decoupled from local precipitation and recharge events but not completely.…”
Section: Introductionmentioning
confidence: 99%